The quality effect on the profitability of US airline companies. Issue 3 (May 2018) - Kalemba, Nicole; Campa-Planas, Fernando
This study was conducted to determine if quality had any effects on US airline economic performance. Therefore, four service quality indexes used in the US air transportation industry were included together with two economic performance indicators, passenger revenues and return on investment (ROI). Longitudinal data from the US airline companies from 2006 to 2015 were used to determine if airline activity or profitability increased when service quality improved. The results of this research demonstrated and confirmed the positive and significant influence of service quality on the ROI of US airline companies. Meanwhile, a non-significant effect was found for quality on airline passenger revenues. As none of the previous research studies have considered the four quality indexes altogether, the findings of this work could encourage airline companies to invest in quality, since this policy can have a positive consequence for their profitability.